IDENTIFIKASI DINAMIKA SPIRITUAL SANTRI YANG MENGALAMI TRANS DISOSIATIF DI PONDOK PESANTREN ANNUQAYAH LUBANGSA PUTRI - Ulfatul Maghfiroh (Living Sufism: Journal of Sufism and Psychotherapy, 2022)
This research is motivated by the researcher's observations on the daily behavior of students who experienced Dissociative Trance Disorder (DTD) in Annuqayah Lubangsa Putri Islamic Boarding School by focusing on their psychic and spiritual aspects. This study aims to reveal two things: first, what are the symptoms and factors that cause dissociative trance experienced by students of Annuqayah Lubangsa Putri Islamic Boarding School, and second, how is the spiritual dynamics of students of Annuqayah Lubangsa Putri who experienced dissociative trance. This study used a qualitative method with a case study approach. To see the spiritual dynamics of the students, Robert Frager's theory was used, namely the development of the nafs, and Sigmund Freud's theory of personality structure to determine the psychological state of the subject. The results of this study indicated several conclusions that dissociative trance does not occur suddenly and not only have a mystical case but is also motivated by internal and external factors. The internal factors of the three subjects are relatively the same. namely stress (conflict or trauma), uncontrollable emotions and physical exhaustion. While the external factors in subjects II and III have in common, namely the presence of interference from immaterial beings, family problems and inappropriate parenting. While the subject I is caused by the conditions of the social environment. Symptoms that appear in the three subjects were initiated by the screams of the one who is in trance, starts to throw tantrums, tends to hurt herself and identifies herself with other people, animals or objects. The spiritual dynamics of the subject can be seen from the development of the nafs. It starts from pre-disorder living adjustments to the disorder seemingly to be a congenital disease. The subject's spirituality starts from the lowest nafs until the subject is able to feel spiritual pleasure and can even feel satisfaction and gratitude for what God has outlined.